The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/15592294.2018.1543507
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs are involved in the hypothalamic leptin sensitivity

Abstract: The central nervous system monitors modifications in metabolic parameters or hormone levels (leptin) and elicits adaptive responses such as food intake and glucose homeostasis regulation. Particularly, within the hypothalamus, pro-opiomelanocortin (POMC) neurons are crucial regulators of energy balance. Consistent with a pivotal role of the melanocortin system in the control of energy homeostasis, disruption of the Pomc gene causes hyperphagia and obesity. Pomc gene expression is tightly controlled by differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…Indeed, monoallelic depletion of Dicer in POMC neurons incurs reduced metabolic rates in mice by reduction of O 2 consumption and CO 2 production. However, food intake is decreased due to elevated leptin sensitivity in POMC neurons demonstrated by increased phosphorylation of signal transducer and activator of transcription 3 (STAT3) in POMC neurons upon leptin administration [22]. Leptin, an adipokine secreted by adipocytes, acts on POMC and AgRP/NPY neurons to suppress food intake and promote energy expenditure [23].…”
Section: Regulation Of Catabolism By Dicer In Thementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, monoallelic depletion of Dicer in POMC neurons incurs reduced metabolic rates in mice by reduction of O 2 consumption and CO 2 production. However, food intake is decreased due to elevated leptin sensitivity in POMC neurons demonstrated by increased phosphorylation of signal transducer and activator of transcription 3 (STAT3) in POMC neurons upon leptin administration [22]. Leptin, an adipokine secreted by adipocytes, acts on POMC and AgRP/NPY neurons to suppress food intake and promote energy expenditure [23].…”
Section: Regulation Of Catabolism By Dicer In Thementioning
confidence: 99%
“…Leptin, an adipokine secreted by adipocytes, acts on POMC and AgRP/NPY neurons to suppress food intake and promote energy expenditure [ 23 ]. The discrepancy that, by manipulation of Dicer, food intake does not coincide [ 10 , 11 , 22 ] might be explained by the fact that partial Dicer defect predominantly affects metabolic rates. And as a compensator, leptin sensitivity is subsequently increased to maintain normal body weight.…”
Section: Regulation Of Catabolism By Dicer In the Central Nervous mentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are a class of endogenous, non-coding small ribonucleic acids containing 21-24 nucleotides. 7 Evidence has indicated that miRNAs involved T he incidence and mortality of cardiovascular diseases keep increasing due to aging population in the intensification, as old patients with aged myocardial are more prone to myocardial infarction (MI) and heart failure. 1,2 After MI, ischemia/reperfusion (I/R) can cause additional injury such as cellular metabolic dysfunction and structural damage due to rapid reperfusion of the ischemic or hypoxia myocardium.…”
mentioning
confidence: 99%
“…It is essential to identify the intracellular mediators that allow these POMC neurons to respond to energy status modifications. In this context, we and others observed that miRNAs can be important intracellular mediators in the modulation of POMC neurons activity [1,[13][14][15][16][17]. So far, only two teams have identified mir-488 as miRNA that physically interact with the 3 UTR of POMC mRNA [29,32].…”
Section: Discussionmentioning
confidence: 98%